Remodeling Multivariate Control Chart by Using Spatial Signed Rank for Detecting Mean Shift in Normal and Non-Normal Processes - Haanchumpol, Thidathip; Sermpongpan, Chatchai (Thailand Statistician, 2023)
This research aimed to modify the traditional multivariate control charts by using the multivariate spatial signed rank under the normal distribution, the t distribution, and the gamma distribution. The performance of the modern multivariate control charts is measured based on the average run length (ARL). The ARL is computed using a Monte Carlo simulation. The Monte Carlo approach is applied to simulate the circumstances via MATLAB software. The spatial signed-rank multivariate exponentially weighted moving average (SSRM) control chart is found to be the most appropriate approach to detect the small mean shifts and the large smoothing parameters of all three distributions. Besides, SSRM is a robust tool for detecting waste and is suitable for most industrial processes.